A bio-based waterborne polyurethane material self-repairing performance enhancer and a process for improving its self-repairing performance

By introducing Lewis acid catalytic mechanism and post-adding self-repair enhancer process into bio-based aqueous polyurethane materials, the contradiction between self-repair performance and mechanical properties is solved, and the coordination of self-repair performance and mechanical properties is achieved. Extend the service life of the material.

CN116790148BInactive Publication Date: 2025-02-11CENT SOUTH UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310783447.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

There is a contradiction between the self-repair performance and mechanical properties of existing bio-based aqueous polyurethane materials, and it is difficult to take into account excellent self-repair performance and high-strength mechanical properties.

Method used

通过引入路易斯酸催化机理,采用后加自修复增强剂工艺,对含有硫代氨基甲酸酯键的生物基水性聚氨酯材料进行自修复性能增强,利用可逆共价键的断裂重排机制,实现材料 Improved self-healing performance.

Benefits of technology

It has achieved the improvement of self-healing performance of bio-based aqueous polyurethane materials, while maintaining high-strength mechanical properties and extending the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116790148B_ABST
    Figure CN116790148B_ABST
Patent Text Reader

Abstract

The present invention discloses a self-repairing performance enhancer for bio-based waterborne polyurethane materials and a process for improving its self-repairing performance. The raw materials of the self-repairing performance enhancer include, by weight, 5 to 10 parts of Lewis acid catalysts and 90 to 95 parts of anhydrous solvents. The waterborne polyurethane coating obtained in the present invention and its self-repairing performance enhancement process are characterized in that the self-repairing monomer introduced into the polyurethane coating can form a reversible dynamic chemical bond thiocarbamate bond or urea bond with isocyanate in the reaction, and these reversible bonds are weak in dynamic characteristics and will not affect the mechanical properties of the material. At the same time, with the subsequent addition of the self-repairing performance enhancer, these dynamic chemical bonds can be promoted to break and rearrange, thereby enhancing the self-repairing performance of the coating and extending the service life of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of waterborne polyurethane materials, and in particular relates to a bio-based waterborne polyurethane material self-repairing performance enhancer and a process for improving the self-repairing performance thereof. Background Art

[0002] With the in-depth promotion of green and sustainable concepts in the field of materials, bio-based waterborne polyurethane materials have been developed on the basis of traditional solvent-based polyurethane materials. Bio-based waterborne polyurethane materials have the mechanical properties of solvent-based materials while further reducing VOCs emissions. The introduction of bio-based components further ensures that the materials have sustainable and developable characteristics. These excellent properties have attracted much attention to bio-based waterborne polyurethane materials, but the materials themselves still have to face the test of different forms of damage such as external collisions, scratches and internal stress during service.

[0003] In order to extend the service life of materials, scientists have learned from nature and proposed a new concept of self-repairing materials by analogy with the self-healing mechanism of animals and plants when facing damage (Polym.Mech.,1970,6:240–244.). With the development of about half a century, the concept of self-repair has been introduced into various material applications. From external self-repair to intrinsic self-repair, the types and forms of self-repairing materials have developed by leaps and bounds. However, some key issues still hinder the promotion and application of self-repairing materials in engineering practice.

[0004] The excellent self-healing properties of self-healing materials are often contradictory to their strong mechanical properties. This is because polymer materials are made of polymer chains entangled with each other or combined through hydrogen bonds, ionic bonds and other interactions. The physical or chemical interactions between these chain segments jointly ensure the mechanical properties of the material, such as Figure 1 After the introduction of external self-repair, the added capsules or fiber vessels will destroy the macroscopic structure of the polymer itself, and the heterogeneous components brought inside the polymer will greatly reduce the performance, such as Figure 1 As shown in (b). Based on the external self-repair, people proposed intrinsic self-repair. Although intrinsic self-repair does not require the addition of heterogeneous materials, it does require the introduction of reversible bonds. The bond energy of these reversible bonds is generally low, so the polymer chain segment breaks and is easier to break from there, such as Figure 1 In addition, the introduction of reversible bonds may also reduce the intermolecular interactions in the polymer segments, further reducing the mechanical properties of the material.

[0005] Chinese invention patent application CN 111849327 A discloses a method for preparing a pH stimulus-responsive intelligent self-warning self-repairing anti-corrosion water-based coating, wherein the water-based polyurethane coating is prepared from pH stimulus-responsive organic-inorganic hybrid hollow microspheres and water-based polyurethane, wherein the amphoteric microspheres are used as a source of self-repairing performance (including corrosion inhibitors and fluorescent probe molecules), which can stimulate the rapid rupture of the microspheres when the coating layer is broken, release the corrosion inhibitor to achieve material self-repair, and release the fluorescent probe molecules to play a warning effect. Although this self-repairing coating with microspheres can achieve a certain degree of material self-repair, its limited number of self-repairs is a major defect, and the nano-microspheres will cause the mechanical properties of the material to decrease, which also limits its further development.

[0006] Chinese invention patent application CN 110028648 A discloses a method for preparing a self-healing waterborne polyurethane, wherein the polyurethane material is a two-component material, which contains a macromolecular diol, a diisocyanate, a small molecule diol containing a furan ring, a hydrophilic chain extender, a capping agent, a catalyst, a neutralizer, deionized water, a diamine chain extender and a maleimide crosslinker. This polyurethane material utilizes the reversible chemical reaction that the furan ring in the waterborne polyurethane reacts with the maleimide in the crosslinker to undergo a DA reaction, giving the polyurethane coating excellent self-healing properties. The obtained material does not require a catalyst, the conditions are mild, the operation is simple, and the repair effect is good. However, a large amount of furan compounds are used in this material, which may pose a hidden danger to the health of construction workers, and the mechanical properties of the material obtained in this invention patent are significantly weakened, which brings another limitation.

[0007] Chinese invention patent application CN 110028686 A discloses a cellulose nanocrystal-enhanced self-healing waterborne polyurethane material and its preparation method. Based on the invention patent CN 110028648 A, the polyurethane material introduces cellulose nanocrystals as a reinforcing phase into the polyurethane. This polyurethane material uses the reversible chemical reaction of DA reaction and uses cellulose nanocrystals rich in hydrogen bonding sites, high aspect ratio, high strength and high modulus as fillers, which gives the polyurethane coating excellent self-healing properties while improving the mechanical properties of the material. However, the material still uses a large amount of furan compounds, which may pose a health hazard to construction workers, and the energy and materials required for the fillers also consume more energy and materials.

[0008] The development of self-healing materials with both excellent self-healing properties and high-strength mechanical properties has great engineering application value, among which bio-based self-healing materials have great potential. However, due to the inherent contradiction between mechanical properties, self-healing properties and bio-based materials, there is still a lack of bio-based materials with coordinated self-healing properties and mechanical strength. Based on the Lewis acid catalysis mechanism, the present invention proposes to enhance the self-healing properties of bio-based waterborne polyurethane materials containing thiocarbamate bonds (urea bonds) as reversible covalent bonds through the process of post-adding self-healing enhancers, so as to ultimately enable the material to have good self-healing properties while maintaining high-strength mechanical properties. Summary of the invention

[0009] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a bio-based waterborne polyurethane material self-healing performance enhancer and a self-healing performance improvement process, so as to achieve the unification of the mechanical properties and self-healing properties of the material, further extend the service life of the polyurethane material, and promote the development of waterborne polyurethane materials.

[0010] In the first aspect, the bio-based waterborne polyurethane material self-healing performance enhancer provided by the present invention comprises the following components, measured by weight: 5 to 10 parts of a Lewis acid catalyst and 90 to 95 parts of an anhydrous solvent; the Lewis acid catalyst is one of dibutyltin dilaurate, zinc acetate, zirconium acetylacetonate, iron acetylacetonate, titanium isopropoxide and hafnium acetylacetonate; the anhydrous solvent is one of anhydrous chloroform and anhydrous dimethyl sulfoxide.

[0011] In a second aspect, the process for improving the self-healing performance of a bio-based waterborne polyurethane material provided by the present invention comprises the following steps:

[0012] S1. Prepare the self-healing performance enhancer as described in the first aspect: mix the Lewis acid catalyst and the anhydrous solvent in a dry environment according to the ratio to obtain a self-healing performance enhancer;

[0013] S2. Spraying or coating the bio-based waterborne polyurethane material on the base material, and drying at 80 to 100° C. for 24 to 48 hours to obtain a dry paint film;

[0014] S3. Spray 0.3-0.5 mL / cm onto the dry paint film prepared in step S2. 2 The self-repairing performance enhancer is added, and the paint film is sent into a vacuum oven, heated to 70-90° C. and dried for 1-3 hours to obtain a polyurethane paint film material with enhanced self-repairing performance that is finally attached to the substrate.

[0015] In some embodiments, the self-healing performance enhancer needs to be stored in a sealed anhydrous environment before use.

[0016] In some embodiments, the raw materials of the bio-based waterborne polyurethane material include the following components by mass: 33 to 50 parts of bio-based polyols, 25 to 40 parts of diisocyanates, 8 to 15 parts of internal emulsifiers, 1 to 5 parts of catalysts, 2 to 15 parts of self-healing monomers, 5 to 15 parts of neutralizers, 0 to 3 parts of fillers, and 0 to 3 parts of pigments.

[0017] In some specific embodiments, the bio-based polyol is castor oil, and its hydroxyl value is 162-168 mgKOH / g; the diisocyanate is any one of isophorone diisocyanate, toluene diisocyanate, and dimethylmethane diisocyanate; the internal emulsifier is any one of dihydroxymethylpropionic acid, dihydroxymethylbutyric acid, 2,3-dihydroxysuccinic acid, carboxyl half-ester diol, 2-sodium sulfonate-1,4-butanediol, and 2,5-dihydroxybenzoic acid; the self-healing monomer is a monomer compound containing a dithiol or amino group, preferably 1,5-pentanedithiol, benzene-1,4-dithiol, 1,4-dihydroxybenzoic acid. Any one of mercaptan, 1,6-hexanedithiol, biphenyl-4,4′-dithiol, 1,2-bis(2-ethoxythiol)ethane and diethylenetriamine, adipic acid diamine, 1,3-phenylenediamine, 1,4-phenylenediamine and 1,6-hexanediamine; the catalyst is one of an organic tin catalyst and a tertiary amine catalyst; the neutralizer is one of triethylamine, triethanolamine, N-methyldiethanolamine, ammonia water, sodium bicarbonate and sodium carbonate; the pigment is one of titanium dioxide, magnesium aluminate, titanium dioxide, carbon black and zinc oxide; the filler is one of calcium carbonate, talcum powder, water-based metallic glitter powder, mica powder and carboxymethyl cellulose.

[0018] In some specific embodiments, the preparation process of the bio-based waterborne polyurethane material comprises the following steps:

[0019] 1) Add bio-based polyol, internal emulsifier and diisocyanate into a three-necked flask, stir at a speed of 180-250 r / min, dry at 90-95° C. for 0.5-1.5 h, add part of the catalyst, stir and react to obtain an intermediate product a;

[0020] 2) adding a self-repairing monomer to the intermediate product a of step 1), and then adding the remaining catalyst, stirring and reacting to obtain an intermediate product b;

[0021] 3) adding a neutralizing agent dropwise to the intermediate product b of step 2), stirring and reacting to obtain a polyurethane prepolymer;

[0022] 4) Adding pigment and filler to the polyurethane prepolymer of step 3), dripping deionized water and increasing the rotation speed for emulsification to obtain a bio-based waterborne polyurethane emulsion.

[0023] In some more specific embodiments, in step 1), the reaction temperature is 75-85° C., the reaction time is 3-4 h, and the stirring speed is 180-250 r / min.

[0024] In some more specific embodiments, in step 2), the reaction temperature is 75-85° C., the reaction time is 0.5-1 h, and the stirring speed is 150-200 r / min.

[0025] In some more specific embodiments, in step 3), the reaction temperature is 25-50° C., the reaction time is 20-30 min, and the stirring speed is 150-200 r / min.

[0026] In some more specific embodiments, in step 4), the volume ratio of the polyurethane prepolymer to deionized water is 1:(3-1); the rotation speed is increased to above 1100 r / min; and the emulsification time is 20-40 min.

[0027] The beneficial effects of the present invention are as follows: 1) The bio-based waterborne polyurethane material of the present invention has high bio-based content, high mechanical properties and low VOCs emissions, and has excellent properties of being green, environmentally friendly and sustainable; 2) The novel self-healing performance improvement process provided by the present invention sprays a self-healing performance enhancer on the surface of the bio-based waterborne polyurethane material, thereby promoting the reversible dynamic chemical bonds (thiourea bonds or polyurea bonds) in the bio-based waterborne polyurethane material to undergo fracture and rearrangement, inducing the enhancement of the self-healing performance of the material without affecting the original mechanical properties of the material, and can extend the service life of the material, which has broad reference significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of the effect of introducing self-healing function into polymer on the mechanical properties of the material;

[0029] Figure 2 A schematic diagram of the preparation process of the bio-based waterborne polyurethane material and the process for improving the self-healing performance of the present invention;

[0030] Figure 3 This is a physical picture of the waterborne polyurethane emulsion prepared in Examples 1 and 2;

[0031] Figure 4 The self-healing performance enhancer prepared in Examples 1-2 is shown in the figure, and the blank solvent is shown in Comparative Examples 1-2.

[0032] Figure 5 Comparison diagram of scratches on waterborne polyurethane films of Examples 1-2 and Comparative Examples 1-2 before and after self-repair. DETAILED DESCRIPTION

[0033] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.

[0034] Example 1

[0035] The raw material ratio of the waterborne polyurethane material in this embodiment is as follows (by mass):

[0036] Castor oil: 2.89 g, hydroxyl value 165 mg KOH / g

[0037] Isophorone diisocyanate: 1.96g

[0038] 1,3-phenylenediamine: 0.17 g

[0039] Dimethylolpropionic acid: 0.51 g

[0040] Dibutyltin dilaurate (organic tin catalyst): 0.15g

[0041] Triethylamine: 0.37 g

[0042] Titanium dioxide: 0.04g

[0043] Talc: 0.02g

[0044] The raw material ratio of the self-repairing performance enhancer is as follows (mass):

[0045] Zinc acetate: 1g

[0046] Anhydrous chloroform: 9g

[0047] The specific implementation steps of this embodiment are as follows:

[0048] 1) First, castor oil, dimethylol propionic acid and isophorone diisocyanate were stirred in a three-necked flask and dried at 90°C for 0.5h. Then, 0.10g of dibutyltin dilaurate was added to the mixture, and the mixture was reacted for 3h at 85°C and 200r / min mechanical stirring speed to obtain intermediate product a. 1,3-phenylenediamine was added to the intermediate product a, and then the remaining 0.05g of dibutyltin dilaurate was added, and the mixture was reacted for 1h at 85°C and 200r / min mechanical stirring speed to obtain intermediate product b. Triethylamine was added dropwise to the intermediate product b, and the mixture was reacted for 30min at 35°C and 200r / min mechanical stirring speed to obtain a polyurethane prepolymer. Titanium dioxide and talcum powder were added to the polyurethane prepolymer, and deionized water was added dropwise. The speed was increased for emulsification. The deionized water was 25 ml, the speed was increased to 1200 r / min, and the emulsification time was 30 min. Finally, a water-based polyurethane emulsion was obtained. The actual emulsion is shown in the figure below. Figure 3 shown.

[0049] 2) Then, zinc acetate is dissolved in anhydrous chloroform, and the completely dissolved solution is sealed and stored. The entire experiment needs to be completed in a dry environment. The self-healing performance enhancer finally obtained is as follows Figure 4 shown.

[0050] 3) The water-based polyurethane emulsion was injected into a tetrafluoroethylene mold, and dried at 80°C for 48 hours to obtain a water-based polyurethane film. The self-healing performance enhancer was then sprayed on the surface of the water-based polyurethane film using a spray pot, and then dried in a vacuum oven at 80°C for 3 hours to obtain a dry film. A 10-15 μm scratch was manually made on the surface of the film with a blade, and the film was placed at 75°C for 30 minutes, and the scratch self-healing condition was observed under an optical microscope. Figure 5 As shown in the figure, by observing the scratch width repair situation, the self-repair performance of the material can be clearly observed. The self-repair performance calculation formula is as follows:

[0051]

[0052] The self-healing performance efficiency is shown in Table 1.

[0053] Comparative Example 1

[0054] This comparative example uses anhydrous chloroform (such as Figure 3 ) was used as a blank control of the self-healing performance enhancer. The influence of the solvent on the material properties was eliminated by comparison to verify the actual influence of the self-healing performance enhancer on the self-healing properties of the waterborne polyurethane in Example 1.

[0055] The specific implementation scheme is as follows: the aqueous polyurethane emulsion in Example 1 is injected into a tetrafluoroethylene mold, and the mold is dried at 80°C for 48 hours to obtain an aqueous polyurethane film; then anhydrous chloroform is sprayed on the surface of the aqueous polyurethane film using a spray pot as a control for spraying the self-repairing performance enhancer in Example 1, and then the film is placed in a vacuum oven at 80°C for 3 hours to obtain a dry film; then a 10-15 μm scratch is manually scratched on the surface of the film with a blade, and the film is placed at 75°C for 30 minutes, and the scratch self-repair is observed by an optical microscope, as shown in FIG. Figure 5 The obtained self-healing performance efficiency is shown in Table 1.

[0056] Example 2

[0057] The raw material ratio of the waterborne polyurethane material in this embodiment is as follows (by mass):

[0058] Castor oil: 1.87 g, hydroxyl value 165 mg KOH / g

[0059] Isophorone diisocyanate: 1.93g

[0060] 1,6-Hexanedithiol: 0.30g

[0061] 2,3-Dihydroxysuccinic acid: 0.56 g

[0062] Triethylenediamine (tertiary amine catalyst): 0.09 g

[0063] Triethylamine: 0.37 g

[0064] Titanium dioxide: 0.15g

[0065] Carboxymethyl cellulose: 0.08g

[0066] The raw material ratio of the self-repairing performance enhancer is as follows (mass):

[0067] Ferrous acetylacetonate: 1g

[0068] Anhydrous chloroform: 9g

[0069] The specific implementation process of this embodiment is as follows:

[0070] 1) First, castor oil, 2,3-dihydroxysuccinic acid and isophorone diisocyanate were stirred in a three-necked flask and dried at 90°C for 0.5h. Then, 0.06g of triethylenediamine was added to the mixture, and the mixture was reacted for 3h at 75°C and 200r / min mechanical stirring speed to obtain intermediate product a. 1,6-hexanedithiol was added to the intermediate product a, and then the remaining 0.03g of triethylenediamine was added, and the mixture was reacted for 1h at 85°C and 200r / min mechanical stirring speed to obtain intermediate product b. Triethylamine was added dropwise to the intermediate product b, and the mixture was reacted for 30min at 35°C and 200r / min mechanical stirring speed to obtain a polyurethane prepolymer. Titanium dioxide and carboxymethyl cellulose were added to the polyurethane prepolymer, and deionized water was added dropwise. The rotation speed was increased for emulsification, wherein the deionized water was 20ml, the rotation speed was increased to 1200r / min, and the emulsification time was 30min. Finally, the water-based polyurethane emulsion is obtained. The actual emulsion is shown in the figure below. Figure 3 shown.

[0071] 2) Then, the ferric acetylacetonate is dissolved in anhydrous chloroform, and the completely dissolved solution is sealed and stored. The entire experiment needs to be completed in a dry environment. The self-healing performance enhancer finally obtained is as follows Figure 4 shown.

[0072] 3) The water-based polyurethane emulsion was injected into a tetrafluoroethylene mold, and dried at 80°C for 48 hours to obtain a water-based polyurethane film. The self-healing performance enhancer was then sprayed on the surface of the water-based polyurethane film using a spray pot, and then dried in a vacuum oven at 80°C for 3 hours to obtain a dry film. A 10-15 μm scratch was manually made on the surface of the film with a blade, and the film was placed at 75°C for 30 minutes, and the scratch self-healing condition was observed under an optical microscope. Figure 5 The obtained self-healing performance efficiency is shown in Table 1.

[0073] Comparative Example 2

[0074] This comparative example uses anhydrous chloroform (such as Figure 3 ) was used as a blank control of the self-healing performance enhancer. The influence of the solvent on the material properties was eliminated by comparison to verify the actual influence of the self-healing performance enhancer on the self-healing properties of the waterborne polyurethane in Example 2.

[0075] The aqueous polyurethane emulsion in Example 2 was injected into a tetrafluoroethylene mold and dried at 80°C for 48 hours to obtain an aqueous polyurethane film. Then, anhydrous chloroform was sprayed on the surface of the aqueous polyurethane film using a spray pot as a control for spraying the self-repairing performance enhancer in Example 2, and then the film was placed in a vacuum oven and dried at 80°C for 3 hours to obtain a dry film. A 10-15 μm scratch was manually scratched on the surface of the film with a blade, and the film was placed at 75°C for 30 minutes, and the scratch self-repair was observed under an optical microscope. Figure 5 The obtained self-healing performance efficiency is shown in Table 1.

[0076] Example 3

[0077] According to the standard ISO1184-1983 "Determination of tensile properties of plastic films", the films of Examples 1 to 2 and Comparative Examples 1 to 2 were tested for mechanical properties using a tensile testing machine; according to the specific requirements of GB / T 6739-2006 "Determination of film hardness by pencil method for paints and varnishes", the hardness of the coating was tested using a pencil scratch hardness tester. The test results of mechanical properties, hardness and self-healing properties are shown in Table 1.

[0078] Table 1 Performance test results of waterborne polyurethane film before and after using self-healing performance enhancer

[0079]

[0080] As shown in Table 1, the tensile strength and hardness of the film material in Examples 1 and 2 sprayed with the self-repairing performance enhancer did not change significantly compared to Comparative Examples 1 and 2 sprayed with anhydrous solvent, indicating that spraying the self-repairing performance enhancer will not affect the mechanical strength of the film material in actual operation. At the same time, the mechanical strength of the film material in the embodiment reached a maximum of 18.2MPa, which can be widely used in many fields with high requirements for material performance.

[0081] As shown in Table 1, with the spraying of the self-repairing performance enhancer, the self-repairing efficiency of Example 1 (Example 2) is increased by 1.33 times (0.96 times) compared with Comparative Example 1 (Comparative Example 2). The results show that the introduction of the self-repairing performance enhancer significantly enhances the self-repairing performance of the bio-based waterborne polyurethane material. Through the self-repairing performance enhancer and the self-repairing performance improvement process proposed in the present invention, the coordinated progress of self-repairing performance and mechanical properties in bio-based waterborne polyurethane is successfully achieved.

[0082] The above embodiments are only for illustrating the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any non-creative changes made on the basis of the technical solution of the present invention in accordance with the technical conception proposed by the present invention shall fall within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.

Claims

1. A process for improving the self-healing performance of a bio-based waterborne polyurethane material, comprising the following steps: S1. Preparation of bio-based waterborne polyurethane material self-healing performance enhancer: The self-repairing performance enhancer comprises the following components by weight: 5-10 parts of a Lewis acid catalyst and 90-95 parts of an anhydrous solvent; the Lewis acid catalyst is one of dibutyltin dilaurate, zinc acetate, zirconium acetylacetonate, iron acetylacetonate, titanium isopropoxide and hafnium acetylacetonate; the anhydrous solvent is one of anhydrous chloroform and anhydrous dimethyl sulfoxide; The Lewis acid catalyst and the anhydrous solvent are mixed uniformly in a dry environment according to a ratio to obtain a self-healing performance enhancer; S2. spraying or coating the bio-based waterborne polyurethane material on the base material, and drying at 80-100° C. for 24-48 hours to obtain a dry paint film; The raw materials of the bio-based waterborne polyurethane material include the following components by weight: 33-50 parts of bio-based polyol, 25-40 parts of diisocyanate, 8-15 parts of internal emulsifier, 1-5 parts of catalyst, 2-15 parts of self-repairing monomer, 5-15 parts of neutralizer, 0-3 parts of filler, and 0-3 parts of pigment; The catalyst is one of an organotin catalyst and a tertiary amine catalyst; S3. Spray 0.3~0.5 mL / cm onto the dry paint film prepared in step S2. 2 The self-healing performance enhancer is added, and the paint film is sent into a vacuum oven, heated to 70-90 °C and dried for 1-3 h to obtain a polyurethane paint film material with enhanced self-healing performance that is finally attached to the substrate.

2. The self-repairing performance improvement process according to claim 1, characterized in that: The bio-based polyol is castor oil, and its hydroxyl value is 162-168 mg KOH / g; the diisocyanate is any one of isophorone diisocyanate, toluene diisocyanate, and dimethylmethane diisocyanate; the catalyst is one of an organic tin catalyst and a tertiary amine catalyst; the neutralizer is one of triethylamine, triethanolamine, N-methyldiethanolamine, ammonia water, sodium bicarbonate, and sodium carbonate; the pigment is one of titanium dioxide, magnesium aluminate, titanium dioxide, carbon black, and zinc oxide; the filler is one of calcium carbonate, talcum powder, water-based metallic glitter, mica powder, and carboxymethyl cellulose.

3. The self-repairing performance improvement process according to claim 1, characterized in that: The internal emulsifier is any one of dihydroxymethylpropionic acid, dihydroxymethylbutyric acid, 2,3-dihydroxysuccinic acid, carboxyl-containing half-ester diol, 2-sodium sulfonate-1, 4-butanediol, and 2,5-dihydroxybenzoic acid; the self-repairing monomer is a monomer compound containing a dithiol or amino group.

4. The self-repairing performance improvement process according to claim 3, characterized in that: The self-healing monomer is any one of 1,5-pentanedithiol, benzene-1,4-dithiol, 1,4-benzenedimethanethiol, 1,6-hexanedithiol, biphenyl-4,4′-dithiol, 1,2-bis(2-ethoxythiol)ethane and diethylenetriamine, adipic acid diamine, 1,3-phenylenediamine, 1,4-phenylenediamine, and 1,6-hexanediamine.

5. The self-repairing performance improvement process according to claim 1, characterized in that: The preparation process of the bio-based waterborne polyurethane material comprises the following steps: 1) Add bio-based polyol, internal emulsifier and diisocyanate into a three-necked flask, stir at 180-250 r / min, dry at 90-95°C for 0.5-1.5h, add part of the catalyst, stir and react to obtain intermediate product a; 2) adding the self-repairing monomer to the intermediate product a of step 1), and then adding the remaining catalyst, stirring and reacting to obtain the intermediate product b; 3) adding a neutralizing agent dropwise to the intermediate product b of step 2), stirring and reacting to obtain a polyurethane prepolymer; 4) Add pigment and filler to the polyurethane prepolymer of step 3), drop deionized water and increase the rotation speed for emulsification to obtain a bio-based waterborne polyurethane emulsion.

6. The self-repairing performance improvement process according to claim 5, characterized in that: In the step 1), the reaction temperature is 75-85°C, the reaction time is 3-4 h, and the stirring speed is 180-250 r / min.

7. The self-repairing performance improvement process according to claim 5, characterized in that: In the step 2), the reaction temperature is 75-85°C, the reaction time is 0.5-1 h, and the stirring speed is 150-200 r / min.

8. The self-repairing performance improvement process according to claim 5, characterized in that: In the step 3), the reaction temperature is 25-50°C, the reaction time is 20-30 min, and the stirring speed is 150-200 r / min.

9. The self-repairing performance improvement process according to claim 5, characterized in that: In the step 4), the volume ratio of the polyurethane prepolymer to deionized water is 1:(3-1); the rotation speed is increased to above 1100 r / min; and the emulsification time is 20-40 min.

Citation Information

Patent Citations

  • Self-repaired waterborne polyurethane material and preparation method thereof

    CN110028648A

  • Cellulose nanocrystal reinforced self-repairing water-based polyurethane material and preparation method thereof

    CN110028686A

  • Preparation method of pH stimuli-responsive intelligent self-early-warning self-repairing anticorrosive water-based coating layer

    CN111849327A

  • Bio-based waterborne polyurethane material with self-repairing performance and preparation method thereof

    CN115197394A